Enhanced interrogation of degraded DNA from human skeletal remains: Increased genetic data recovery using the expanded CODIS loci, multiple sex determination markers, and consensus testing - Ambers, Angie; Zeng, Xiangpei; Votrubova, Jitka; Vanek, Daniel (Anthropologischer Anzeiger; Bericht uber die biologisch-anthropologische Literatur, 2019)
Skeletal remains are among the most difficult types of samples encountered in forensic DNA casework and historical investigations due to prolonged exposure to environmental insults. DNA extracted from bone often is degraded, in low quantities, and contains co-purified inhibitors from the surrounding soil and/or burial vault material. When sexually dimorphic skeletal elements are not recovered, determining the sex of a decedent can be challenging. With unidentified human skeletal remains, genetic data often are evaluated in concert with anthropological analyses, as well as other types of metadata, to improve confidence in making associations or for positive identifications. This study evaluated a multi-faceted molecular genetic approach to increasing the amount of data that can be recovered from degraded skeletal remains. Results demonstrate that using a newer-generation multiplex (GlobalFiler™) with an expanded set of highly discriminatory DNA markers - combined with co-amplification of three different sex-determining loci, one additional PCR cycle, and testing multiple cuttings from the same bone or multiple regions within a skeleton - can improve reliability and accuracy in skeletal remains identifications by providing data concordance.
Keywords: Reproducibility of Results; antropologie; DNA fingerprinting; mikrosatelitní repetice; tělesné pozůstatky; Humans; Anthropology; Consensus; Microsatellite Repeats; reprodukovatelnost výsledků; Body Remains; DNA; DNA Fingerprinting; lidé; konsensus